Study on Efficacy and Safety of Terbinafine Vs. Itraconazole in the Treatment of Tinea Pedis (TAJ: Journal of Teachers Association, 2023)
Background: Tinea pedis is a dermatophytosis of the feet usually occurs between the toes with the webspace between the fourth and fifth digits but, in many cases, may appear as an extensive pattern on the bottom and sides of the feet. Terbinafine and itraconazole were evaluated with the efficacy/effectiveness and toxicity in the systemic treatment of Tinea pedis and compared with each other.  Objective: To compare the efficacy and safety of terbinafine vs. itraconazole in treating tinea pedis.Materials and Methods: A total of 50 patients were selected, and they were divided into groups (group-A and group B), each of which included 25 patients. Group A was given oral Terbinafine 250 mg daily for two weeks. Group B was given oral Itraconazole 200mg daily for the same duration. Patients were observed for the efficacy and side effects of the trial medicines. A baseline complete blood picture, liver and renal function test, and urine analysis were done and repeated frequently during therapy.Results: Most patients were in the fourth decade in both groups, and the male-to-female ratio was almost 4:1. Two groups of people were studied: group-A with terbinafine 250 mg daily and group B with itraconazole 200 mg daily for 14 days. Evaluated weekly during treatment and 02 weeks after cessation of therapy, and finally on 08th week to see the clinical improvement and adverse effects. The clinical response was found in chronic hyperkeratotic type: 08/08, 08/08; chronic interdigital type: 07/07, 07/06; vesico-bullous type: 06/05, 06/05; Mixed type: 04/03, 03/02 in group-A and group-B respectively. On average, 92% clinical improvement was found in group-A and 84% in group B. Most patients had nausea (20.0%) followed by 08% diarrhea in group A. On the other hand, in group B, most patients had nausea (28.0%), followed by 4.0% fatigue and 4.0% diarrhea, and only 01 patient found elevated liver enzyme but did not exceed the upper limit. 80% of patients in the terbinafine group had transient, mild to moderate nausea.Conclusion: No significant differences in efficacy and toxicity were found between terbinafine and itraconazole groups. Terbinafine may represent a good alternative for treating Tinea Pedis in patients who cannot take itraconazole or other available drugs due to contraindications.TAJ 2022; 36: No-1: 75-82